Vulnerability of solar energy infrastructure and output to climate change - Patt, Anthony; Pfenninger, Stefan; Lilliestam, Johan (Climatic Change, 2013)
This paper reviews the potential vulnerability of solar energy systems to future extreme event risks as a consequence of climate change. We describe the three main technologies likely to be used to harness sunlight-thermal heating, photovoltaic (PV), and concentrating solar power (CSP)-and identify critical climate vulnerabilities for each one. We then compare these vulnerabilities with assessments of future changes in mean conditions and extreme event risk levels. We do not identify any vulnerabilities severe enough to halt development of any of the technologies mentioned, although we do find a potential value in exploring options for making PV cells more heat-resilient and for improving the design of cooling systems for CSP. © 2013 Springer Science+Business Media Dordrecht.
CRIS-Team Scopus Importer:2023-06-14